2022
DOI: 10.1002/ajb2.16092
|View full text |Cite
|
Sign up to set email alerts
|

Evolvability and constraint in the evolution of three‐dimensional flower morphology

Abstract: Premise: Flower phenotypes evolve to attract pollinators and to ensure efficient pollen transfer to and from the bodies of pollinators or, in self-compatible bisexual flowers, between anthers and stigmas. If functionally interacting traits are genetically correlated, response to selection may be subject to genetic constraints. Genetic constraints can be assessed by quantifying standing genetic variation in (multivariate) phenotypic traits and by asking how much the available variation is reduced under specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Conflicting selection through the male and female sexual functions of hermaphroditic plants can provide an explanation for the phenotypic ‘maladaptation’ often observed in plant populations (Armbruster et al ., 2009; Brady et al ., 2019; Opedal et al ., 2022). However, our results illustrate that patterns of selection are not necessarily different between the sexes, despite the expected greater variance in male than female fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting selection through the male and female sexual functions of hermaphroditic plants can provide an explanation for the phenotypic ‘maladaptation’ often observed in plant populations (Armbruster et al ., 2009; Brady et al ., 2019; Opedal et al ., 2022). However, our results illustrate that patterns of selection are not necessarily different between the sexes, despite the expected greater variance in male than female fitness.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that herkogamy can rapidly evolve in response to environmental changes, suggesting that variation in herkogamy in related species and populations may result from variation in pollinator communities and other selective factors. More recent work (Opedal et al 2022) suggests that the evolvability of certain floral traits varies throughout phenotypic space and that particular trait combinations may be subject to strong genetic constraints that stall evolution towards optimum self-pollination rates. This work on the potential genetic constraints of functionally interactive floral traits (Opedal et al 2022) reinforces herkogamy's high level of independent evolutionary potential.…”
Section: Function and Evolution Of Herkogamymentioning
confidence: 99%
“…More recent work (Opedal et al 2022) suggests that the evolvability of certain floral traits varies throughout phenotypic space and that particular trait combinations may be subject to strong genetic constraints that stall evolution towards optimum self-pollination rates. This work on the potential genetic constraints of functionally interactive floral traits (Opedal et al 2022) reinforces herkogamy's high level of independent evolutionary potential.…”
Section: Function and Evolution Of Herkogamymentioning
confidence: 99%
“…Therefore, test of a genetic constraint hypothesis will need to incorporate the amount of evolutionary change and/or time since divergence, as originally proposed (Schluter, 1996;Hunt, 2007;Hansen & Voje, 2011). In this sense, joint examination of evolvability and the amount of phenotypic divergence (Bolstad et al, 2014;Opedal et al, 2022) seems to be a sensible approach. Univariate tests based on the present theories will be one of the possible toolkits for testing genetic constraints.…”
Section: Testing Constraint Hypothesismentioning
confidence: 99%